1998
DOI: 10.1562/0031-8655(1998)068<0101:aocawp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ceramide Accumulation with Photodynamic Treatment-Induced Cell Death

Abstract: Ceramide, a stress-induced second messenger, has been associated with apoptosis in several malignant and non-malignant cell lines. We have shown that photodynamic treatment (PDT), using the phthalocyanine photosensitizer Pc 4 (HOSiPcOSi[CH3]2[CH2]3N[CH3]2), causes increased ceramide generation and subsequent induction of apoptosis in L5178Y-R (LY-R) mouse lymphoma cells. To test further if ceramide generation accompanies photocytotoxicity, we treated various cell lines with a PDT dose producing a 99-99.9% loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…26,[98][99][100][101][102] In addition to their roles in chemotherapeutic cell death, ceramides were also shown to be associated with the photodynamic therapy-induced and gamma radiationinduced apoptosis in different leukemia cell lines. 103,104 As supportive to those observations, suppression of sphingomyelin synthase converting ceramide into SM was shown to potentiate the effects of photodynamic therapy. 105 However, according to the cell type used in the experiment, observations for roles of ceramides may differ.…”
Section: Bioactive Sphingolipids In Hematological Malignanciessupporting
confidence: 56%
“…26,[98][99][100][101][102] In addition to their roles in chemotherapeutic cell death, ceramides were also shown to be associated with the photodynamic therapy-induced and gamma radiationinduced apoptosis in different leukemia cell lines. 103,104 As supportive to those observations, suppression of sphingomyelin synthase converting ceramide into SM was shown to potentiate the effects of photodynamic therapy. 105 However, according to the cell type used in the experiment, observations for roles of ceramides may differ.…”
Section: Bioactive Sphingolipids In Hematological Malignanciessupporting
confidence: 56%
“…The sphingolipid ceramide has proven to be a powerful second-signal effector molecule that regulates diverse cellular processes including apoptosis, cell senescence, the cell cycle, and cellular differentiation. Ceramide has been shown to activate a number of enzymes involved in stress signaling cascades including both protein kinases and protein phosphatases [34]. Dolgachev et al [35] showed that the oxidative stress induced by phthalocyanine (Pc4)-PDT in Jurkat human T lymphoma and CHO cells was accompanied by increases in ceramide with a concomitant decrease in sphingomyelin.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Ceramidedependent induction of apoptosis was observed in Photodynamic therapy different PDT models (Separovic et al, 1997;1998;. Interestingly, in RIF-1 cells an increase in ceramide production following PDT did not augment cell death, suggesting a dual role of these substances in the tumor cell metabolism (Separovic et al, 1998). Niemann-Pick (N-P) human lymphoblasts that lack SMases exposed to Pc4-mediated PDT showed an increased survival rate.…”
Section: Signaling Mechanisms In Tumor Cells Exposed To Pdt Lipid Metmentioning
confidence: 99%